2019
DOI: 10.1002/joa3.12284
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS and subclinical left ventricular dysfunction in individuals with preserved ejection fraction: A speckle‐tracking echocardiographic study

Abstract: Introduction Fragmented QRS (fQRS) complex on routine 12‐lead electrocardiogram (ECG) predicts adverse outcomes in patients with cardiovascular diseases. In addition, it has been found to be associated with subclinical myocardial dysfunction in chronic diseases. We sought to investigate the relationship between the presence of fQRS with the myocardial functions in individuals free from known systemic cardiovascular diseases. Methods In a case‐control study, we evaluated normal individuals from March 2017 to Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 37 publications
2
9
1
Order By: Relevance
“…In our study, the mean age of sample was 52.9 ± 6.7 years and 54% was male. Clinical character of our participants showed that heart rate was 80.6 ± 12.4 beat per min, SBP was 116 ± 7.1 mm Hg and DBP was 75.1 ± 5.8 mm Hg in contrast with Dehghani et al, patients with fragmented QRS clinical characters were 76.5 ± 9.4 beat per min, SBP 118.5 ± 10.5 mm Hg and DBP was 70.4 ± 7.3 mm Hg (13) .…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…In our study, the mean age of sample was 52.9 ± 6.7 years and 54% was male. Clinical character of our participants showed that heart rate was 80.6 ± 12.4 beat per min, SBP was 116 ± 7.1 mm Hg and DBP was 75.1 ± 5.8 mm Hg in contrast with Dehghani et al, patients with fragmented QRS clinical characters were 76.5 ± 9.4 beat per min, SBP 118.5 ± 10.5 mm Hg and DBP was 70.4 ± 7.3 mm Hg (13) .…”
Section: Discussioncontrasting
confidence: 82%
“…which supported by Bayramoğlu et al (3) , study whom found that patients with fQRS complex had EF of 58.9 ± 3.8%, LVESD was 3.3 ± 0.6 cm, LVEDD 4.5 ± 0.3 cm, intraventricular septum thickness 10.3 ± 0.6mm and posterior wall thickness was 10.6 ± 0.9 mm. And study of Dehghani et al (13) found that in patients with positive fQRS complex had EF of 59.6 ± 2.4%, LVEDD 4.8 ± 0.3cm, intraventricular septum thickness 1±0.1mm and posterior wall thickness was 0.9 ± 0.08 mm. In study of Yaman et al (12) , patients with fQRS complex had EF of 61.94± 2.18%, LVEDD 4.54±0.3 cm, LVESD was 3.14±0.28 cm, intraventricular septum thickness 0.94±0.18 mm and posterior wall thickness was 0.9 ± 0.11 mm.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Notably, almost all of these studies assessed patients with declined and reduced ejection fraction or impaired LV contractile function rather than healthy individuals or in those with relatively preserved ejection fraction. Dehghani et al reported in a case‐control study (age‐ and sex‐matched) of a healthy population that fQRS was associated with lower subclinical myocardial contractility marker of global ventricular longitudinal strain (GLS). By using speckle‐tracking, a highly sensitive marker for detecting systolic myocardial dysfunction even prior to overt chamber dilation.…”
mentioning
confidence: 99%